Design of broadband absorptive optimum frequency selective rasorber without loaded circuit elements - Özdin, Mustafa; Orak, Salim; Erken, Faruk (Elsevier BV, 2020)
Abstract In this work, unlike conventional ones, an optimum rasorber was designed which does not require circuit elements loaded by soldering. With high physical protection and wide absorption band, this proposed rasorber is suitable for stealthy antenna radomes. This structure is easy to manufacture as the absorption and frequency selectivity are achieved only by resistive and conductive square patch elements integrated into the dielectric layers. Firstly, using computer simulation results, predetermined value sets of equivalent circuit elements of the impedance of a frequency selective surface (FSS) are obtained depending on the dimensions in a unit cell. Then, the reflection and transmission coefficients of the whole structure are expressed as the functions of all variables in the rasorber. The transmission coefficient calculation is carried out with a newly introduced formulation. The optimum values of the variables are determined by using multi-objective optimization. A broadband rasorber prototype containing three resistive FSS and a conductive FSS is manufactured and the test results are shown quantitatively. The designed structure transmits 4.2 GHz operating frequency with slight attenuation and it provides reflection less than −10 dB in the 8–23.4 GHz band and less than −15 dB in the 8.6–21.4 GHz band.
Keywords: 7. Clean energy